Compliance in handling of donated raw breast milk to human milk banks regarding microbiological quality - Jaísa Oliveira Chaves; Angélica Maria de Freitas Fernandes; Paola Machado Parreiras; Maria Cristina Passos; Luciana Rodrigues da Cunha; Camila Carvalho Menezes (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: microbiological quality of raw human milk (HM) from donors at the HMB (Human Milk Bank) of Santa Casa de Misericórdia de Ouro Preto was evaluated. Methods: the microbiological quality of milk from each of 10 donors in triplicate (30 samples) was evaluated by enumeration of Staphylococcus aureus and total aerobic mesophiles (surface plating) and total and thermotolerant coliforms (Most Probable Number - MPN). A questionnaire and a checklist were applied after the end of sample collection to verify the compliance of milk extraction and storage procedures by the donors. Results: inadequacies in the procedures for expression and storage of donated HM were observed. The presence of all microorganisms studied were verified in the milk of all donors, and in some cases exceeded the safety limits. The checklist indicated that some necessary hygienic-sanitary procedures were not carefully performed, making it important to properly guide the donors. Conclusions: this study points to an unfavorable scenario for the safety and quality of donated HM, and it is important to encourage further studies to be conducted so that the Brazilian network of HMB adopts stricter criteria for instructions on procedures and support for HM donors.